Home My Page Projects Code Snippets Project Openings diderot
Summary Activity Tracker Tasks SCM

SCM Repository

[diderot] Diff of /branches/charisee_dev/src/compiler/high-il/normalize-ein.sml
ViewVC logotype

Diff of /branches/charisee_dev/src/compiler/high-il/normalize-ein.sml

Parent Directory Parent Directory | Revision Log Revision Log | View Patch Patch

branches/charisee/src/compiler/high-il/normalize-ein.sml revision 2452, Sat Oct 5 00:43:58 2013 UTC branches/charisee_dev/src/compiler/high-il/normalize-ein.sml revision 3441, Wed Nov 18 00:24:04 2015 UTC
# Line 5  Line 5 
5    
6      structure E = Ein      structure E = Ein
7      structure P=Printer      structure P=Printer
8        structure F=Filter
9        structure G=EpsHelpers
10        structure Eq=EqualEin
11        structure R=RationalEin
12    
13      in      in
14    
15        val testing=0
16  (*Flattens Add constructor: change, expression *)      fun err str=raise Fail (String.concat["Ill-formed EIN Operator",str])
17  fun mkAdd [e]=(1,e)      fun mkProd e= F.mkProd e
18      | mkAdd(e)=let      fun filterSca e=F.filterSca e
19      fun flatten((i, (E.Add l)::l'))= flatten(1,l@l')      fun mkAdd e=F.mkAdd e
20          |flatten(i,((E.Const c):: l'))=      fun filterGreek e=F.filterGreek e
21              if (c>0.0 orelse c<0.0) then let      fun mkapply e= derivativeEin.mkapply e
22                      val(b,a)=flatten(i,l') in (b,[E.Const c]@a) end      fun testp n=(case testing
23              else flatten(1,l')          of 0=> 1
24          | flatten(i,[])=(i,[])          | _ =>(print(String.concat n);1)
         | flatten (i,e::l') =  let  
                     val(b,a)=flatten(i,l') in (b,[e]@a) end  
   
      val (b,a)=flatten(0,e)  
     in case a  
      of [] => (1,E.Const(1.0))  
                 | [e] => (1,e)  
                 | es => (b,E.Add es)  
                 (* end case *)  
      end  
   
   
 fun mkProd [e]=(1,e)  
     | mkProd(e)=let  
     fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')  
         |flatten(i,((E.Const c)::l'))=  
                 if(c>0.0 orelse  0.0>c) then (3,[E.Const 0.0])  
                 else flatten(i,l')  
          | flatten(i,[])=(i,[])  
          | flatten (i,e::l') =  let val(a,b)=flatten(i,l') in (a,[e]@b) end  
      val (change,a)=flatten(0,e)  
      in if(change=3) then (1,E.Const(0.0))  
         else case a  
         of [] => (1,E.Const(0.0))  
         | [e] => (1,e)  
         | es => (change, E.Prod es)  
         (* end case *)  
          end  
   
 (*  
   
 fun mkEps(e)= (case e  
     of E.Apply(E.Partial [E.V a], E.Prod( e2::m ))=> (0,e)  
      | E.Apply(E.Partial [E.V a,E.V b], E.Prod( (E.Epsilon(i,j,k))::m ))=>  
         (if(a=i andalso b=j) then (1,E.Const(0.0))  
         else if(a=i andalso b=k) then (1,E.Const(0.0))  
         else if(a=j andalso b=i) then (1,E.Const(0.0))  
         else if(a=j andalso b=k) then (1,E.Const(0.0))  
         else if(a=k andalso b=j) then (1,E.Const(0.0))  
         else if(a=k andalso b=i) then (1,E.Const(0.0))  
         else (0,e))  
     |_=> (0,e)  
     (*end case*))  
   
   
   
 fun mkSumApply(E.Sum(c,E.Apply(d, e))) = (case e  
     of E.Tensor(a,[])=> (0,E.Const(0.0))  
     | E.Tensor _=> (0,E.Sum(c,E.Apply(d,e)))  
     | E.Field _ =>(0, E.Sum(c, E.Apply(d,e)))  
     | E.Const _=> (1,E.Const(0.0))  
     | E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(d, e))) l))  
     | E.Sub(e2, e3) =>(1, E.Sub(E.Sum(c,E.Apply(d, e2)), E.Sum(c,E.Apply(d, e3))))  
     | E.Prod((E.Epsilon c)::e2)=> mkEps(E.Apply(d,e))  
     | E.Prod[E.Tensor(a,[]), e2]=>  (0, E.Prod[ E.Tensor(a,[]), E.Sum(c,E.Apply(d, e2))]  )  
     | E.Prod((E.Tensor(a,[]))::e2)=>  (0, E.Prod[E.Tensor(a,[]), E.Sum(c,E.Apply(d, E.Prod e2))] )  
     | E.Prod es =>   (let  
         fun prod [e] = (E.Apply(d, e))  
         | prod(e1::e2)=(let val l= prod(e2) val m= E.Prod[e1,l]  
             val lr=e2 @[E.Apply(d,e1)]   val(b,a) =mkProd lr  
             in ( E.Add[ a, m] ) end)  
         | prod _= (E.Const(1.0))  
             in (1, E.Sum(c,prod es))  end)  
     | _=> (0,E.Sum(c,E.Apply(d,e)))  
25      (*end case*))      (*end case*))
26    
27     *)      val zero=E.B(E.Const 0)
28        fun setConst e = E.setConst e
29        fun setNeg e  =  E.setNeg e
30  fun rmEpsIndex(_,_,[])=[]      fun setExp e  =  E.setExp e
31  | rmEpsIndex([],[],cs)=cs      fun setDiv e= E.setDiv e
32  | rmEpsIndex([],m ,e1::cs)=[e1]@rmEpsIndex(m,[],cs)      fun setSub e= E.setSub e
33  | rmEpsIndex(i::ix,rest ,(E.V c)::cs)=      fun setProd e= E.setProd e
34      if(i=c) then rmEpsIndex(rest@ix,[],cs)      fun setAdd e= E.setAdd e
     else rmEpsIndex(ix,rest@[i],(E.V c)::cs)  
   
   
 (* Transform eps to deltas*)  
 fun epsToDels(E.Sum(count,E.Prod e))= let  
     fun doubleEps((E.Epsilon (a,b,c))::(E.Epsilon(d,e,f))::es,eps,e3)=  
         let  
   
         (*Function is called when eps are being changed to deltas*)  
         fun createDeltas(i,s,t,u,v, e3)= let  
   
             (*remove index from original index list*)  
             (*currrent, left, sumIndex*)  
   
             val s'= rmEpsIndex([i,s,t,u,v],[],count)  
             val s''=[E.V s, E.V t ,E.V u, E.V v]  
             val deltas= E.Sub(  
                     E.Sum(s'',E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3)),  
                     E.Sum(s'',E.Prod([E.Delta(E.V s,E.V v), E.Delta(E.V t,E.V u)]@e3)))  
   
             in (case (eps,s')  
                 of ([],[]) =>(1,deltas)  
                 |([],_)=>(1,E.Sum(s',deltas))  
                 |(_,[])=>(1,E.Prod(eps@[deltas]))  
                 |(_,_) =>(1, E.Sum(s', E.Prod(eps@[deltas])))  
                    )  
              end  
   
         in if(a=d) then createDeltas(a,b,c,e,f, e3)  
            else if(a=e) then createDeltas(a,b,c,f,d, e3)  
            else if(a=f) then createDeltas(a,b,c,d,e, e3)  
            else if(b=d) then createDeltas(b,c,a,e,f, e3)  
            else if(b=e) then createDeltas(b,c,a,f,d,e3)  
            else if(b=f) then createDeltas(b,c,a,d,e,e3)  
            else if(c=d) then createDeltas(c,a,b,e,f,e3)  
            else if(c=e) then createDeltas(c,a,b,f,d,e3)  
            else if(c=f) then createDeltas(c,a,b,d,e,e3)  
            else (0,E.Const 0.0)  
         end  
     fun findeps(e,[])= (e,[])  
       | findeps(e,(E.Epsilon eps)::es)=  findeps(e@[E.Epsilon eps],es)  
       | findeps(e,es)= (e, es)  
   
   
     fun dist([],eps,rest)=(0,eps,rest)  
      | dist([e],eps,rest)=(0,eps@[e],rest)  
      | dist(c1::current,eps,rest)=let  
             val(i, exp)= doubleEps(c1::current,eps,rest)  
         in  (case i of 1=>(i,[exp],[E.Const 2.0])  
             |_=> dist(current, eps@[c1],rest))  
         end  
   
     val (es,rest)=findeps([],e)  
   
     in  
         dist(es,[],rest)  
     end  
   
35    
36  fun rmIndex(_,_,[])=[]      (*mkSum:sum_indexid list * ein_exp->int *ein_exp
37      | rmIndex([],[],cs)=cs      *distribute summation expression
38      | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)      *)
39      | rmIndex(i::ix,rest ,c::cs)=      fun mkSum(sx1,b)=(case b
40          if(i=c) then rmIndex(rest@ix,[],cs)          of E.Lift e         => (1,E.Lift(E.Sum(sx1,e)))
41          else rmIndex(ix,rest@[i],c::cs)          | E.Tensor(_,[])    => (1,b)
42            | E.B _             => (1,b)
43  (* Apply deltas to tensors/fields*)          | E.Opn(E.Prod, es)   => filterSca(sx1,es)
44  fun reduceDelta(E.Sum(c,E.Prod p))=let          | _                 => (0,E.Sum(sx1,b))
45            (*end case*))
     fun findDeltas(dels,rest,E.Delta d::es)= findDeltas(dels@[E.Delta d], rest, es)  
     | findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)  
     | findDeltas(dels,rest,es)=  (dels,rest,es)  
   
   
     fun distribute(change,d,dels,[],done)=(change,dels@d,done)  
     | distribute(change,[],[],e,done)=(change,[],done@e)  
     | distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=  
         if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])  
         else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)  
     | distribute(change,E.Delta(i,j)::ds,dels,E.Field(id,[tx])::es,done)=  
         if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Field(id,[i])])  
         else distribute(change,ds,dels@[E.Delta(i,j)],E.Field(id,[tx])::es,done)  
     | distribute(change,d,dels,e::es,done)=distribute(change,dels@d,[],es,done@[e])  
   
     val (dels,eps,es)=findDeltas([],[],p)  
     val (change,dels',done)=distribute([],dels,[],es,[])  
     val index=rmIndex(change,[],c)  
46    
47        (*mkprobe:ein_exp* ein_exp-> int ein_exp
48        *rewritten probe
49        *)
50        fun mkprobe(b,x)=let
51            val (c,rtn)=(case b
52                of (E.B _)              => (0,b)
53                | E.Tensor _            => err("Tensor without Lift")
54                | E.G _                 => (0,b)
55                | E.Field _             => (0,E.Probe(b,x))
56                | E.Lift e1             => (1,e1)
57                | E.Conv _              => (0,E.Probe(b,x))
58                | E.Partial _           => err("Probe Partial")
59                | E.Apply _             => (0,E.Probe(b,x))
60                | E.Probe _             => err("Probe of a Probe")
61                | E.Value _             => err("Value used before expand")
62                | E.Img _               => err("Probe used before expand")
63                | E.Krn _               => err("Krn used before expand")
64                | E.Sum(sx1,e1)         => (1,E.Sum(sx1,E.Probe(e1,x)))
65                | E.Op1(op1, e1)        => (1,E.Op1(op1, E.Probe(e1,x)))
66                | E.Op2(op2, e1,e2)     => (1,E.Op2(op2, E.Probe(e1,x), E.Probe(e2,x)))
67                | E.Opn(opn, [])        => err("Probe of empty operator")
68                | E.Opn(opn, es)        => (1,E.Opn(opn, List.map(fn e1=> E.Probe(e1,x)) es))
69                (*end case*))
70    in    in
71         (change, E.Sum(index,E.Prod (eps@dels'@done)))              (c,rtn)
72    end    end
73    
74  fun mkApply2(E.Apply(d,e))=(case e      (* normalize: EIN->EIN
75      of E.Tensor(a,[])=>(1,E.Const 0.0)      * rewrite body of EIN
76      | E.Const _ =>(1,E.Const 0.0)      * note "c" keeps track if ein_exp is changed
     | E.Add l => (1,E.Add(List.map (fn e => E.Apply(d, e)) l))  
     | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(d, e2), E.Apply(d, e3)))  
     | E.Prod(E.Tensor(a,[])::e2)=>(1,E.Prod[E.Tensor(a,[]),E.Apply(d,e)])  
     | E.Prod [e1]=>(1,E.Apply(d,e1))  
     | E.Prod es=> (let  
         fun prod [e1] =E.Apply(d,e1)  
         | prod(e1::e2)=(let  
             val l= prod(e2) val m= E.Prod[e1,l]  
             val lr=e2 @[E.Apply(d,e1)] val(b,a) =mkProd lr  
             in  E.Add[a,m]  
             end)  
         in (1,prod es) end)  
     |_=>(0,E.Apply(d,e))  
     (* end case*))  
   
 fun mkSumApply2(E.Sum(c,E.Apply(E.Partial d,e)))=(case e  
     of E.Const _=>(1,E.Const 0.0)  
     | E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(E.Partial d, e))) l))  
     | E.Sub(e2, e3) =>(1, E.Sub(E.Sum(c,E.Apply(E.Partial d, e2)), E.Sum(c,E.Apply(E.Partial d, e3))))  
     | E.Prod(E.Tensor(a,[])::e2)=>(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,E.Prod e2))])  
     | E.Prod [e1]=>(1,E.Sum(c,E.Apply(E.Partial d,e1)))  
     | E.Prod es =>(let  
         fun prod (change,rest, sum,partial,[]) = (change,E.Sum(sum,E.Apply(E.Partial partial,E.Prod rest)))  
         | prod (change,rest, sum,partial,E.Epsilon(i,j,k)::ps)= let  
             fun matchprod(2,_,_,_)= 1 (*matched 2*)  
             | matchprod(num,_,_,[])=0  
             | matchprod(0,_,_,[eps])=0  
             | matchprod(num,[],rest,eps::epsx)=  
                 matchprod(num,rest,[],epsx)  
             | matchprod(num,E.V p::px,rest,eps::epsx)=  
                 if(p=eps) then matchprod(num+1,px,rest,epsx)  
                 else matchprod(num,px,rest@[E.V p], eps::epsx)  
             | matchprod(num,p::px,rest,eps)=  
                 matchprod(num,px,rest,eps)  
   
             val change'= matchprod(0,d,[],[i,j,k])  
             in (case change'  
                 of 1 => (1,E.Const 0.0)  
                 | _ =>prod(change,rest@[E.Epsilon(i,j,k)],sum,partial,ps))  
             end  
         | prod (change,rest, sum,partial,E.Delta(i,j)::ps)=let  
             fun applyDelPartial([],_)=(0,[])  
             | applyDelPartial(p::px,r)=  
                 if(j=p) then (1,r@[i]@px)  
                 else  applyDelPartial(px,r@[p])  
   
             val (change',px)=applyDelPartial(d,[])  
   
             in (case change'  
                 of 1 => (let val index=rmIndex([j],[],sum)  
                     in prod(1,rest, index,px, ps) end )  
                 | _ => prod(change,rest@[E.Delta(i,j)], sum,partial, ps)  
                 (*end case*)) end  
   
         | prod (change,rest,sum, partial,e::es)= prod(change,rest@[e],sum,partial,es)  
   
         val (change,exp) = prod(0,[],c, d, es)  
   
         in  
             (change,exp)  
         end)  
     | _=>(0,E.Sum(c,E.Apply(E.Partial d,e)))  
         (* end case*))  
   
 (*  
 E.Sum(c,Apply(d,e))  
     try E.Sum(c,e)=> E.Sum(c',e')  
     ==>    E.Sum(c',E.Apply(d,e'))  
         E.Apply(d,e')=> E.Apply(d',e'')  
     ==>E.Sum(c',E.Apply(d',e'')  
77  *)  *)
78        fun normalize (ee as Ein.EIN{params, index, body},args) = let
 (*Apply normalize to each term in product list  
 or Apply normalize to tail of each list*)  
 fun normalize (Ein.EIN{params, index, body}) = let  
79        val changed = ref false        val changed = ref false
80        fun rewriteBody body = (case body        fun rewrite body =(case body
81               of E.Const _=> body          of E.B _                                => body
82                | E.Tensor _ =>body                | E.Tensor _ =>body
83            | E.G _                                 => body
84                    (************** Field Terms **************)
85                | E.Field _=> body                | E.Field _=> body
86                | E.Kernel _ =>body          | E.Lift e1                             => E.Lift(rewrite e1)
87                | E.Delta _ => body          | E.Conv _                              => body
               | E.Value _ =>body  
               | E.Epsilon _=>body  
   
               | E.Neg e => E.Neg(rewriteBody e)  
               | E.Add es => let val (change,body')= mkAdd(List.map rewriteBody es)  
                    in if (change=1) then ( changed:=true;body') else body' end  
               | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)  
               | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)  
88                | E.Partial _=>body                | E.Partial _=>body
89                | E.Conv (V, alpha)=> E.Conv(rewriteBody V, alpha)          | E.Apply(E.Partial [],e1)              => e1
90                | E.Probe(u,v)=>  E.Probe(rewriteBody u, rewriteBody v)          | E.Apply(E.Partial d1, e1)             =>
91                | E.Image es => E.Image(List.map rewriteBody es)              let
92                val e2 = rewrite e1
93                  (*Product*)                  val (c,e3)=mkapply(E.Partial d1,e2)
94                | E.Prod [e1] => rewriteBody e1                  val _= testp["\nafter apply:",P.printbody body,"-->",P.printbody e3]
95                | E.Prod(e1::(E.Add(e2))::e3)=>                  in
96                     (changed := true; E.Add(List.map (fn e=> E.Prod([e1, e]@e3)) e2))                      (case c of 1=>(changed:=true;e3)| _ =>e3 (*end case*))
               | E.Prod(e1::(E.Sub(e2,e3))::e4)=>  
                    (changed :=true; E.Sub(E.Prod([e1, e2]@e4), E.Prod([e1,e3]@e4 )))  
               | E.Prod [E.Partial r1,E.Conv(f,deltas)]=>  
                    (changed :=true;E.Conv(f,deltas@r1))  
               | E.Prod (E.Partial r1::E.Conv(f,deltas)::ps)=>  
                    (changed:=true;  
                     let val (change,e)=mkProd([E.Conv(f,deltas@r1)]@ps)  
                     in e end)  
               | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>  
                     if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0.0))  
                     else body  
   
              | E.Prod(E.Partial r1::E.Partial r2::p)=>  
                    (changed:=true;E.Prod([E.Partial(r1@r2)]@p))  
               | E.Prod(e::es)=>let  
                     val e'=rewriteBody e  
                     val e2=rewriteBody(E.Prod es)  
                     val(a,b)=(case e2 of E.Prod p'=> mkProd([e']@p')  
                         |_=>mkProd [e',e2])  
                     in b  
97                     end                     end
98            | E.Apply _                             => err " Not well-formed Apply expression"
99            | E.Probe(e1,e2)              =>
100                let
101                    val (c',b')=mkprobe(rewrite e1,rewrite e2)
102                in (case c'
103                    of 1=> (changed:=true;b')
104                    | _ => b'
105                    (*end case*))
106                end
107                (************** Field Terms **************)
108            | E.Value _                             => err "Value before Expand"
109            | E.Img _                               => err "Img before Expand"
110            | E.Krn _                               => err "Krn before Expand"
111                (************** Sum **************)
112    
113            | E.Sum([],e1)                           => (changed:=true;rewrite e1)
114            | E.Sum(sx1,e1)                            => let
115                    val e2=rewrite e1
116                    val (c,e')=mkSum(sx1,e2)
117                    val _= testp["\nafter mksum:\n\t",P.printbody body,"\n\t-->",P.printbody e2,"\n\t-->",P.printbody e']
118                    in
119                    (case c of 0 => e'|_ => (changed:=true;e'))
120                    end
121                (*************Algebraic Rewrites Op1 **************)
122    
123                (*Apply*)          | E.Op1(E.Neg,e1)                       => (case e1
124                | E.Apply(E.Partial [],e)=> e              of E.Op1(E.Neg,e2)                  => rewrite e2
125                | E.Apply(E.Partial p, e)=>let              | E.B(E.Const 0)                    =>(changed:=true;zero)
126                      val body'=E.Apply(E.Partial p, rewriteBody e)              | _                                 => E.Op1(E.Neg,rewrite e1)
127                      val (c, e')=mkApply2(body')              (*end case*))
128                  in (case c of 1=>(changed:=true;e')          | E.Op1(op1,e1)                         => E.Op1(op1,rewrite e1)
129                      | _ =>e') end              (*************Algebraic Rewrites Op2 **************)
130                | E.Apply(e1,e2)=>E.Apply(rewriteBody e1, rewriteBody e2)          | E.Op2(E.Sub,e1,e2)                        => (case (e1,e2)
131                of (E.B(E.Const 0),_)                   => (changed:=true;setNeg(rewrite e2))
132                | (_,E.B(E.Const 0))                     => (changed:=true;rewrite e1)
133                | _                                 => setSub(rewrite e1, rewrite e2)
134                (*end case*))
135            | E.Op2(E.Div,e1,e2)                        =>(case (e1,e2)
136                of (E.B(E.Const 0),_)                    => (changed:=true;zero)
137                |(E.Op2(E.Div,a,b), E.Op2(E.Div,c,d))   => rewrite(setDiv(setProd[a,d],setProd[b,c]))
138                |(E.Op2(E.Div,a,b), c)   =>  rewrite (setDiv(a, setProd[b,c]))
139                | (a,E.Op2(E.Div,b,c))                   => rewrite (setDiv(setProd[a,c],b))
140                |  _                        => setDiv(rewrite e1, rewrite e2)
141                (*end case*))
142                (*************Algebraic Rewrites Opn **************)
143            | E.Opn(E.Add,es)          => let
144                val (change,body')= mkAdd(List.map rewrite es)
145                in if (change=1) then ( changed:=true;body') else body' end
146    
147                (* Sum *)          (*************Product**************)
148                | E.Sum([],e)=> (changed:=true;rewriteBody e)          | E.Opn(E.Prod,[])                                 => err "missing elements in product"
149                | E.Sum(_,E.Const c)=>(changed:=true;E.Const c)          | E.Opn(E.Prod,[e1])                               => rewrite e1
150                | E.Sum(c,(E.Add l))=> (changed:=true;E.Add(List.map (fn e => E.Sum(c,e)) l))          | E.Opn(E.Prod,[E.Op1(E.Sqrt,s1),E.Op1(E.Sqrt,s2)])=>
151                | E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>              if(Eq.isBodyEq(s1,s2)) then (changed :=true;s1)
152                     let val (i,e,rest)=epsToDels(body)              else let
153                     in (case (i, e,rest)                  val a=rewrite (E.Op1(E.Sqrt,s1))
154                          of (1,[e1],_) =>(changed:=true;e1)                  val b=rewrite (E.Op1(E.Sqrt,s2))
155                          |(0,eps,[])=>body                  val  (_,d)=mkProd ([a,b])
156                          |(0,eps,rest)=>(let                  in d
157                              val p'=rewriteBody(E.Prod rest)                  end
158                              val p''= (case p' of E.Prod p=>p |e=>[e])          (*************Product EPS **************)
159                              val(a,b)= mkProd (eps@p'')          | E.Opn(E.Prod,(E.G(E.Epsilon e1)::ps))=> let
160                              in E.Sum(c,b) end              val E.G(E.Epsilon(i,j,k))=E.G(E.Epsilon e1)
161                              )              val eps1=E.G(E.Epsilon(i,j,k))
162                          |_=>body)              val p1=List.hd(ps)
163                     end              in (case ps
164                | E.Sum(c, E.Prod(E.Delta d::es))=>let                  of (E.Apply(E.Partial d,e)::es)=>let
165                      val (change,a)=reduceDelta(body)                      val change= G.matchEps(0,d,[],[i,j,k])
166                      val (change',body')=(case a                      in case (change,es)
167                          of E.Prod p=> mkProd p                          of (1,_)    => (changed:=true; zero)
168                          |_=> (0,a))                          | (_,[])    => setProd[eps1,rewrite p1]
169                     in (case change of []=>body'|_=>(changed:=true;body')) end                          | (_,_)     => let
170                | E.Sum(c,E.Apply(d,e))=>let                              val a=rewrite(setProd([p1]@es))
171                      val(c',e')=mkSumApply2(body)                              val (_,b)=mkProd [eps1,a]
172                  in (case c' of 1=>(changed:=true;e') |_=>e')                              in b end
173                        end
174                    | (E.Conv(V,alpha, h, d)::es)=>let
175                        val change= G.matchEps(0,d,[],[i,j,k])
176                        in case (change,es)
177                            of (1,_)    => (changed:=true; E.Lift zero )
178                            | (_,[])    => setProd[eps1,p1]
179                            | (_,_)     => let
180                                val a=rewrite(setProd([p1]@es))
181                                val (_,b) = mkProd [eps1,a]
182                                in b end
183                        end
184                    | [E.Tensor(_,[E.V i1,E.V i2])] =>
185                        if(j=i1 andalso k=i2) then (changed :=true;zero) else body
186                    | _  => (case (G.epsToDels(eps1::ps))
187                        of (1,e,[],_,_)       => (changed:=true;e)(* Changed to Deltas*)
188                        | (1,e,sx,_,_)        => (changed:=true;E.Sum(sx,e))
189                        | (_,_,_,_,[])        =>  body
190                        | (_,_,_,epsAll,rest) => let
191                            val p'=rewrite(setProd rest)
192                            val(_,b)= mkProd(epsAll@[p'])
193                            in b end
194                        (*end case*))
195                    (*end case*))
196                  end                  end
197                | E.Sum(c,e)=>E.Sum(c,rewriteBody e)          | E.Opn(E.Prod,E.Sum(c1,e1)::E.Sum(c2,e2)::es)=>(case (e1,e2,es)
198                of (E.Opn(E.Prod,E.G(E.Epsilon e1)::es1),E.Opn(E.Prod,E.G(E.Epsilon e2)::es2),_) =>
199                    (case G.epsToDels([E.G(E.Epsilon e1), E.G(E.Epsilon e2)]@es1@es2@es)
200                        of (1,e,sx,_,_)=> (changed:=true; E.Sum(c1@c2@sx,e))
201                        | (_,_,_,_,_)=>let
202                            val eA=rewrite(E.Sum(c1,setProd(E.G(E.Epsilon e1)::es1)))
203                            val eB=rewrite(setProd(E.Sum(c2,setProd(E.G(E.Epsilon e2)::es2))::es))
204                            val (_,e)=mkProd([eA,eB])
205                            in  e end
206                    (*end case*))
207                | (_,_,[]) =>let
208                    val (_,b)=mkProd[rewrite(E.Sum(c1,e1)), rewrite(E.Sum(c2,e2))]
209                    in b end
210                |  _ =>let
211                    val e'=rewrite (E.Sum(c1,e1))
212                    val e2=rewrite(E.Opn(E.Prod,E.Sum(c2,e2)::es))
213                    val(_,b)=(case e2
214                        of E.Opn(E.Prod, p')=> mkProd([e']@p')
215                        | _ =>mkProd [e',e2])
216                    in b end
217                (*end case*))
218            | E.Opn(E.Prod,E.G(E.Delta d)::es)=> (case es
219                of [E.Op1(E.Neg, e1)]=> (changed:=true;setNeg(setProd[E.G(E.Delta d), e1]))
220                | _=>   let
221                    val (pre',eps, dels,post)= filterGreek(E.G(E.Delta d)::es)
222                    val _= testp["\n\n Reduce delta--",P.printbody(body)]
223                    val (change,a)=G.reduceDelta(eps, dels, post)
224                    val _= testp["\n\n ---delta moved--",P.printbody(a)]
225                    in (case (change,a)
226                        of (0, _)=> setProd [E.G(E.Delta d),rewrite(setProd es)]
227                        | (_, E.Opn(E.Prod, p))=>let
228                            val (_, p') = mkProd p
229                            in (changed:=true;p') end
230                        | _ => (changed:=true;a )
231              (*end case*))              (*end case*))
232                    end
233                (*end case*))
234          | E.Opn(E.Prod,[e1,e2])=> let
235                val (_,b)=mkProd[rewrite e1, rewrite e2]
236                in b end
237          | E.Opn(E.Prod,e1::es)=>let
238                val e'=rewrite e1
239                val e2=rewrite(setProd es)
240                val(_,b)=(case e2
241                    of E.Opn(Prod, p')=> mkProd([e']@p')
242                    |_=>mkProd [e',e2])
243                in b end
244        (*end case*))
245    
246    
247        fun loop body = let      val _=testp["\n******** Start Normalize: \n",P.printerE ee,"\n*****\n"]
248              val body' = rewriteBody body      fun loop(body ,count) = let
249            val _= testp["\n\n N =>",Int.toString(count),"--",P.printbody(body)]
250            val body' = rewrite body
251              in              in
252                if !changed                if !changed
253                     then (changed := false; print " \n \t => \n \t ";print( P.printbody body');print "\n";loop body')              then  (changed := false ;loop(body',count+1))
254                  else body'              else (body',count)
255              end              end
256      val b = loop body  
257        val (b,count) = loop(body,0)
258        val _ =testp["\n Out of normalize \n",P.printbody(b),
259            "\n    Final CounterXX:",Int.toString(count),"\n\n"]
260      in      in
261      ((Ein.EIN{params=params, index=index, body=b}))          (Ein.EIN{params=params, index=index, body=b},count)
262      end      end
263  end  end
264    

Legend:
Removed from v.2452  
changed lines
  Added in v.3441

root@smlnj-gforge.cs.uchicago.edu
ViewVC Help
Powered by ViewVC 1.0.0